1989
DOI: 10.1111/j.1365-2958.1989.tb00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of ceil division genes in Escherichia coli

Abstract: The complete Escherichia coli ftsQ coding sequence, together with part of the ftsA coding sequence, has been cloned upstream of the lacZ open reading frame in a lambda-vector (lambda JFL100). Cells which are lysogenic for lambda JFL100 transcribe the cloned lacZ from promoter(s) within the ftsQ and ftsA sequences. The level of beta-galactosidase produced is dependent on growth rate (and/or cell size) and is derepressed in an ftsA-deficient mutant. Transcription during the cell cycle is restricted to the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
3

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 16 publications
2
51
3
Order By: Relevance
“…We conclude that the FtsA, FtsQ, FtsI (PBP3), and FtsZ proteins do not exert any transcriptional control on theftsZ gene, in contradiction with other reports (3,5).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…We conclude that the FtsA, FtsQ, FtsI (PBP3), and FtsZ proteins do not exert any transcriptional control on theftsZ gene, in contradiction with other reports (3,5).…”
Section: Resultscontrasting
confidence: 54%
“…In an independent study, using the same ftsZ::lacZ fusion but a different experimental system, others have recently reported that ftsZ transcription takes place only at the time of septation initiation (3). One difference between their study and the present work is the selection by these authors of small cells from a sucrose gradient to obtain a synchronous population; we are currently investigating the possible effects of osmotic shock on ftsZ expression.…”
Section: Discussioncontrasting
confidence: 39%
“…Other estimates of the relative strength of these promoters, based on studies with transcriptional fusions (Yi et al, 1985;Wang et al, 1991;Flä rdh et al, 1997), found about 60% of the total ftsZ mRNA species started from pZ4-pZ3-pZ2-'pZ1', compared with 92% in our study (Table 4). However, the strength of several of these promoters has been shown to vary considerably with growth rate and with growth phase (Dewar et al, 1989;Aldea et al, 1990;Robin et al, 1990;García-Lara et al, 1996;Flärdh et al, 1997). We therefore suspect that the differences in values found by various groups are likely to result from differences in growth phase.…”
Section: Discussionmentioning
confidence: 99%
“…FtsZ is distributed randomly in the cytoplasm between successive divisions but condenses to form a ring around the cell center at the onset of septation (4). The relative rate of ftsZ expression is inversely correlated with growth rate: when the growth rate decreases, ftsZ expression increases (2,17,38). The ppGpp pool size is also inversely correlated with growth rate (10) minimal medium (33) supplemented with glucose (0.4%), thiamine (10 ,ug/ml), thymine (100 ,ug/ml), and serine, glycine, and methionine (100 ,ug/ml each); relA mutants cannot grow on this medium unless isoleucine and valine (100 ,ug/ml each) are added (49,50).…”
mentioning
confidence: 99%
“…2) shows that all the genes can be transcribed from two promoters located in the ddlB gene, and ftsZ has four additional promoters within the ftsA gene (2,39,40). The expression of ftsZ is inversely correlated with growth rate (2,17,38). The P01 promoter contains a so-called "gearbox" sequence, which is found in other promoters inversely regulated by growth rate (1) and, in one case, has been shown to be essential for this regulation (2).…”
mentioning
confidence: 99%